Combination effects of Pistachio hull and carfilzomib on NF-κB p65, MDR1, MRP1, and Caspase3 gene expression in breast cancer cell line - Zahra Mirzaei; Sadegh Zarei; Ahmadreza Sayadi; Reza Hosseiniara; Mojgan Noroozi Karimabad; Mehdi Mahmoodi (BMC Complementary Medicine and Therapies)
Abstract Objective This study aimed to investigate the synergistic effects of the chemotherapy drug Carfilzomib (CFZ) and Pistachio hull extract on the SK-BR3 breast cancer cell line. Methods In this experimental study, we evaluated the effect of Pistachio hull extract and CFZ as standalone treatments on cell viability using the MTT assay at 24- and 48-hours post-treatment. Following this, we conducted combination therapy analyses to assess the potential synergistic relationship between Pistachio hull extract and CFZ after 24- and 48-hours of treatment on both the SK-BR3 breast cancer cell line and the MCF10A normal cell line. We utilized real-time PCR to measure the expression levels of MDR1, MRP1, NF-κB p65, and Caspase3 genes. Additionally, the NF-κB p65 transcription factor was evaluated using ELISA after 24- and 48-hours. Results The MTT assay revealed IC50 values of 2.014 mg/mL and 1.031 mg/mL in the SK-BR3 cell line, and 3.265 mg/mL and 2.994 mg/mL in the MCF10A cell line at 24- and 48-hours post-treatment with Pistachio hull extract. CFZ concentrations of 0.181 × 10− 3 mg/mL and 0.0057 × 10− 3 mg/mL in the SK-BR3 cell line, as well as 5.54 × 10− 3 mg/mL and 2.51 × 10− 3 mg/mL in the MCF10A cell line, inhibited growth by up to 50%. The analysis of combination therapy indicated a synergistic effect between the two treatments after both 24- and 48-hours of exposure. Real-time PCR results demonstrated significant alterations in the expression of MDR1, MRP1, NF-κB p65, and Caspase3 genes, along with changes in NF-κB p65 protein levels in both cell lines following treatment with Pistachio hull extract, CFZ, or their combination compared to the control group (p < 0.05). Conclusion The findings highlight the effectiveness of CFZ as a proteasome inhibitor when used in conjunction with Pistachio hull extract in breast cancer cell lines. Therefore, both CFZ and Pistachio hull extract, whether administered alone or in combination, represent promising molecular targets for breast cancer treatment.